PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Ariyani, Vivi; Kurniawati, Dyah; Sukoco, Y. Djoko (Widya Warta, 2020)
This study aimed to analyze the effect of profitability on firm value with capital structure as an intervening variable. It used a purposive sampling technique, and the object in this study was the financial company in the period of 2015-2016, with the type of panel data of 170. The results of this study were profitability had a positive effect on capital structure and firm value directly. In contrast, the capital structure as an intervening variable of the effect of profitability on firm value was not proven.